2020
DOI: 10.1017/ice.2020.1300
|View full text |Cite
|
Sign up to set email alerts
|

Five-year outcome of peripherally inserted central catheters in adults: a separated infectious and thrombotic complications analysis

Abstract: Objective: To assess infectious and thrombotic complications of peripherally inserted central catheters (PICCs) in adults. Design: A 5-year prospective cohort study. Setting: Tertiary-care teaching hospital in Seville, Spain. Patients: Adult patients undergoing PICC insertion. Methods: Catheter-associated bloodstream infection (CABSI) including catheter-related bloodstream infection (CRBSI), primary bacteremia (PB), and upper extremit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
5
0
4
Order By: Relevance
“…First, the single centre design of the study could limit extrapolation of the results. Second, the relatively small size of our cohort limited the weight of some factors such as BMI > 40 kg/m 2 , number of lumen or total parenteral nutrition which are recognized at risk factors for CR-BSI [ 40 , 57 ]. However, to the best of our knowledge, this study is the first to analyse the association between clinical signs and PR-BSI.…”
Section: Discussionmentioning
confidence: 99%
“…First, the single centre design of the study could limit extrapolation of the results. Second, the relatively small size of our cohort limited the weight of some factors such as BMI > 40 kg/m 2 , number of lumen or total parenteral nutrition which are recognized at risk factors for CR-BSI [ 40 , 57 ]. However, to the best of our knowledge, this study is the first to analyse the association between clinical signs and PR-BSI.…”
Section: Discussionmentioning
confidence: 99%
“…ICU-acquired bloodstream infections were reported to have an increased incidence in COVID-19 patients admitted to the ICU [ 46 , 47 ]. In a matched-case cohort study, COVID-19 increased the daily risk of developing ICU-acquired bloodstream infections with an HR of 4.5 (95% CI: 1.82–11.16; p = 0.001), with coagulase-negative Staphylococci being the microorganism most frequently identified among COVID-19 patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neonates have low immunity and poor resistance to infection, and they are a high-risk group of nosocomial infections. PICC placement can increase the risk of nosocomial infections [13]. A multi-center case-control study [14] have showed that after PICC catheterization for more than 2 weeks, the risk of CRBSI continues to increase with the extension of PICC stay.…”
Section: Discussionmentioning
confidence: 99%